Rapid initiation of antiretrovirals at a syringe services program for people with HIV who inject drugs - Marina Plesons; William Yang; Griffin M. Sansbury; Edward Suarez; Chevel Collington; Elisha Ekowo; Katrina Ciraldo; Teresa Chueng; David P. Serota; David W. Forrest; Tyler S. Bartholomew; Hansel E. Tookes (Annals of Medicine)
Background People who inject drugs (PWID) living with HIV are less likely to receive care at early disease stages and have low rates of viral suppression. This study examined the feasibility and acceptability of rapid antiretroviral therapy (ART) initiation among PWID with HIV at a syringe services program (SSP) and assessed retention in care after transition to a traditional HIV clinic.Patients/Materials and Methods A mixed-methods single-arm pilot study was conducted at an SSP in Miami, Florida. Participants with HIV viral load >200 copies/mL were immediately connected with an HIV care provider and received HIV care and peer navigation at the SSP for 6 months, then were transitioned to a traditional HIV clinic. Demographic data were abstracted from the SSP’s administrative records. Laboratory assessments and qualitative interviews were conducted at 1, 3, 6, 9, and 12 months.Results Sixty-nine percent, 70%, and 69% of participants were virally suppressed (<200 copies/mL) at 1, 3, and 6 months, respectively. Following transition to a traditional HIV clinic, viral suppression remained high at 74% and 79% at 9 and 12 months, respectively. Themes were identified on: 1) barriers to care in traditional HIV clinics, 2) the SSP as a ‘safe haven’, 3) benefits of the rapid ART initiation program, 4) acceptability of telehealth, and 5) persistent barriers to engaging in HIV care.Conclusion Rapid ART initiation for PWID at an SSP was acceptable and feasible and showed preliminary effectiveness in achieving HIV viral suppression and sustaining it after transition to a traditional HIV clinic.